Occurrence of Heat-Resistant Mold Ascospores in Pineapple and Sugarcane Field Soils in Thailand - Maneeboon, Thanapoom; Sangchote, Somsiri; Hongprayoon, Ratchanee; Chuaysrinule, Chananya; Mahakarnchanakul, Warapa (International Journal of Microbiology, 2023)
Heat-resistant molds (HRMs) are important spoilage fungi of heat-processed fruit products worldwide. Ascospores of HRMs are widely distributed in the soil in which fruits are grown and are often found associated with raw fruit materials. To date, there is little available information on the distribution of HRMs in the soil and on their heat resistance. Thus, this study determined the presence and characterized the heat resistance of HRMs in soil samples from pineapple and sugarcane fields in Thailand. HRMs were detected in all soil samples, and the most dominant species was Aspergillus with 50–99.2% relative abundance. Other isolates, in descending order of frequency, were Penicillium, Talaromyces, Hamigera, and Paecilomyces. Then, 100 representative HRM isolates were identified based on a combination of morphological characteristics and ITS sequences. They were classified into 5 genera and 24 species. The heat resistance of ascospores aged 30 days produced by selected HRMs was qualitatively determined in a glucose-buffered solution. Based on their log reductions after heat shock at 75°C for 30 min, they were classified as less, moderately, or highly heat-resistant ascospores. HRMs belonging to A. chevalieri, A. denticulatus, A. siamensis, A. laciniosus, A. fennelliae, A. spinosus, Paec. niveus, H. pallida, and T. macrosporus produced high heat-resistant ascospores. In addition, soil physicochemical properties significantly influenced the prevalence of HRMs, depending on the fungal genus. The thermal resistance of ascospores was significantly and positively correlated to available phosphorus, whereas it was negatively correlated to soil pH. The results of this study confirmed the presence of HRMs in soils and potential HRM contamination, especially in fruits growing in acidic or high-nutrient soils, or both.